Seasonal–interannual–decadal variations of sea level in the South China Sea and connections with the tropical–subtropical Pacific - Juan Li; Wei Tan; Wenjin Sun; Lina Yang; Lei Lin; Qingjun Fu (International Journal of Climatology, 2023)
Different timescale contributions to the sea‐level variation in the South China Sea (SCS) are evaluated in this paper. On seasonal timescale, the large variance of the sea‐level anomaly (SLA) could account for more than 70% of the monthly sea‐level variation in the western shallow continental shelf and the area of Luzon cold eddy. Besides, the seasonal explained variance percentage (skill) has 2 weak centres (50%–70%) off eastern Vietnam, which is related to the summertime eddy pair in the SCS. On interannual‐to‐decadal (low‐frequency) timescale, the skill has two large‐value regions (Zone A and Zone B). Zone A is characterized by double centres off eastern Vietnam, but the meridional position of the double centres is farther north than that of the eddy pair. The skill in Zone A is in the range of 35%–55%, and about 50%–70% of the low‐frequency variation comes from the steric effect. Zone B is off the west coast of the Philippines. The skill in Zone B increases southward, and it is dominated by the wind‐induced dynamic process which is attributed to the remote Rossby wave from the tropical Pacific. Based on the S‐EOF analysis, the SEOF‐1 mode mainly portrays the decadal variation of the SLA, while the SEOF‐2 mode reflects the interannual variation of the SLA. In Zone B, almost all of the low‐frequency variation could be attributed to ENSO and PDO, especially to PDO which has a larger contribution. However, the double centres in Zone A are governed by the SCS summer monsoon, instead of ENSO and PDO.